Respuesta :
radius=sqrt(2^2+9^2)
r=9.22
equation
(x+3)^2+(y-2)^2=9.22^2
(x+3)^2+(y-2)^2=85
r=9.22
equation
(x+3)^2+(y-2)^2=9.22^2
(x+3)^2+(y-2)^2=85
[tex](x-h)^2+(y-k)^2=r^2[/tex]
center is (h,k) and radius is r
so
given center=(-3,2)=(h,k)
[tex](x-(-3))^2+(y-2)^2=r^2[/tex]
[tex](x+3)^2+(y-2)^2=r^2[/tex]
find r^2
ok, (6,4) is a point
sub 6 for x and 4 for y and evaluate
[tex](6+3)^2+(4-2)^2=r^2[/tex]
[tex](9)^2+(2)^2=r^2[/tex]
[tex]81+4=r^2[/tex]
[tex]85=r^2[/tex]
the equation is
[tex](x+3)^2+(y-2)^2=85[/tex]
center is (h,k) and radius is r
so
given center=(-3,2)=(h,k)
[tex](x-(-3))^2+(y-2)^2=r^2[/tex]
[tex](x+3)^2+(y-2)^2=r^2[/tex]
find r^2
ok, (6,4) is a point
sub 6 for x and 4 for y and evaluate
[tex](6+3)^2+(4-2)^2=r^2[/tex]
[tex](9)^2+(2)^2=r^2[/tex]
[tex]81+4=r^2[/tex]
[tex]85=r^2[/tex]
the equation is
[tex](x+3)^2+(y-2)^2=85[/tex]